Using Sanitary Survey Findings to Identify Risk Management Challenges. Issue 5 (31st May 2022) - Heinrich, Austin; Renwick, Deborah Vacs; Weisman, Richard J.; Greene, Ashley; Regli, Stig; Roland, Kevin; Rotert, Kenneth
Key Takeaways: Sanitary survey data can be broadly evaluated to understand the most prevalent issues occurring within public water systems. The most commonly identified deficiencies are associated with monitoring and reporting, finished water storage, and treatment. Reviewing sanitary survey findings and common deficiencies may help officials proactively determine water system infrastructure issues and utility training needs.